Improving attendance for breast screening among recent non-attenders: a randomised controlled trial of two interventions in primary care. - Bankhead, C; Richards, S; Peters, T; Sharp, D; Hobbs, F; Brown, J; Roberts, L; Tydeman, C; Redman, V; Formby, J; Wilson, S; Austoker, J (2001)
OBJECTIVES: To examine the effectiveness and cost-effectiveness of two primary care based interventions aimed at increasing breast screening uptake for women who had recently failed to attend. SETTING: 13 General practices with low uptake in the second round of breast screening (below 60%) in north west London and the West Midlands, United Kingdom. Participants were women in these practices who were recent non-attenders for breast screening in the third round. METHODS: Pragmatic factorial randomised controlled trial, with people randomised to a systematic intervention (general practitioner letter), an opportunistic intervention (flag in women's notes prompting discussion by health professionals), neither intervention, or both. Outcome measures were attendance for screening 6 months after randomisation and cost-effectiveness of the interventions. RESULTS: 1,158 Women were individually randomised as follows: 289 control; 291 letter; 290 flag; 288 both interventions. Attendance was ascertained for 1,148 (99%) of the 1,158 women. Logistic regression adjusting for the other intervention and practice produced an odds ratio (OR) for attendance of 1.51 (95% confidence interval (95% CI 1.02 to 2.26; p=0.04) for the letter, and 1.39 (95% CI 0.93 to 2.07; p=0.10) for the flag. Health service costs/ additional attendance were 35 pounds (letter) and 65 pounds (flag). CONCLUSIONS: Among recent non-attenders, the letter was effective in increasing breast screening attendance. The flag was of equivocal effectiveness and was considerably less cost-effective than the letter.